Apaydin Classification of Spreader Flaps Updated - Capelleras, Marta; Saghir, Meshari; Apaydin, Fazil (Facial Plastic Surgery, 2024)
The use of spreader flaps (SFs) is very helpful in middle vault reconstruction. The aim of the study was to evaluate the versatility of Apaydin classification of SFs on a patient population. This was a retrospective analysis which included 120 rhinoplasty cases. Thorough preoperative planning adhering to precision profileplasty principles was conducted for all patients. The study employed six primary variants of SFs. SFs' types were utilized as follows: type 1 in 41 patients (34.2%), type 2 in 2 patients (1.7%), type 3A in 38 patients (31.7%), types 3B and 3D in 10 cases each (8.3%), type 3C in 2 cases (1.7%), type 4 in 5 cases (4.2%), type 5 in 7 cases (5.8%), and type 6 in 5 cases (4.2%). This study highlights that different SF techniques should be tailored according to the need of the patient when dealing with middle vault reconstruction during reduction rhinoplasty.
Keywords: spreader flap; middle vault; rhinoplasty